1997
DOI: 10.1023/a:1018841402133
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this study was to study sugar maldigestion/malabsorption in patients with functional dyspepsia using H2 breath testing. End-expiratory breath H2 after separate challenges with lactose (25 g), fructose (25 g), and sorbitol (5 g) were used to determine malabsorption, as well as small bowel transit time (SBTT). Five hundred twenty patients with functional dyspepsia received all three challenges. Smaller groups were also tested after lactulose (10 g, N = 36) and glucose (50 g, N = 90) challenges. Fructo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Variation in the magnitude of the response may signify individual differences in fructose sensing and signaling mechanisms, including differences in rates of fructose absorption or metabolism and rates of FGF21 secretion or clearance. For example, it is known that the efficiency of intestinal fructose absorption varies widely across individuals and approximately half the population cannot completely absorb a 25 g fructose load [30,31] . Also, the quantity of fructose in the diet can impact the ability to absorb fructose in subsequent meals [32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in the magnitude of the response may signify individual differences in fructose sensing and signaling mechanisms, including differences in rates of fructose absorption or metabolism and rates of FGF21 secretion or clearance. For example, it is known that the efficiency of intestinal fructose absorption varies widely across individuals and approximately half the population cannot completely absorb a 25 g fructose load [30,31] . Also, the quantity of fructose in the diet can impact the ability to absorb fructose in subsequent meals [32] .…”
Section: Discussionmentioning
confidence: 99%
“…We chose to administer 75 g of fructose in order to match the carbohydrate load of a standard oral glucose tolerance test although we recognize that this exceeds the amount of fructose typically ingested in a single meal. Limitations in fructose absorption can contribute to functional gastrointestinal symptoms [30,31,33] . However, few of our subjects reported symptoms and symptoms did not correlate with the FGF21 response.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, other scientific studies confirmed that lactose malabsorption is often accompanied by fructose malabsorption [ 1 ]. The study published by Mishkin et al [ 18 ] found that both food intolerances were present concomitantly in 60% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Fructose is a six–carbon monosaccharide molecule naturally present in a great variety of daily foods, such as fruits, vegetables, and honey [ 56 ]. It is also produced through enzymatic processing of corn as high fructose corn syrup (HFCS), which is increasingly used in the food industry as a cheaper, tasteless, readily available sweetener in many products, such as sodas, candies, and artificial fruit juices [ 57 ]. Furthermore, this monosaccharide is also present as disaccharide, the sucrose, in complex with glucose [ 58 ].…”
Section: Non-genetic Etiology Carbohydrate Intolerancesmentioning
confidence: 99%
“…In specific conditions, GLUT-2 can be expressed on the apical membrane. Fructose malabsorption should not be confused with hereditary fructose intolerance (a metabolic disease whose incidence is estimated to be 1 in 25,000 individuals) in which a lack of functional aldolase B results in an accumulation of fructose-1-phosphate in the liver, kidneys, and intestine [ 57 ], causing hypoglycemia, nausea, bloating, abdominal pain, diarrhea, and vomiting [ 57 ]. A useful test for diagnosis of fructose malabsorption is the hydrogen breath test [ 58 ], by which the H 2 produced is measured noninvasively in collected samples of expired breath after the ingestion of a standardized dose of 0.5 g/kg of fructose to a maximum of 25 g dissolved in water (sensitivity and specificity both 80% to 90%) [ 14 ].…”
Section: Non-genetic Etiology Carbohydrate Intolerancesmentioning
confidence: 99%